Aplicação de antioxidantes naturais na indústria de alimentos: avaliação química e de percepção do consumidor - Bordim, Jéssica (2020)
One of the great challenges that industrial research has faced in recent years is the search for natural antioxidants aimed at their application in food, cosmetics and pharmaceutical products. Natural antioxidants come from products of plant origin such as fruits, vegetables, legumes, herbs, seeds and industrial waste. These are intended to preserve food by reducing oxidation. Therefore, the first objective of this study was to explore the cognitive assessment of food antioxidants by consumers, using the qualitative technique word association. Consumers have demonstrated prior knowledge about issues related to food antioxidants, natural or not. There was a potential use of natural antioxidants in the food industry, judging by the perception of consumers who cognitively related to positive aspects of health and food safety. The second objective was to verify the antioxidant activity of the ethanol extracts of Moringa oleifera leaves, propolis and grape marc in order to use them in foods aiming at replacing synthetic antioxidants. The extracts were used in chicken pate and the parameters of TBARS, N-BVT, pH and color were monitored during 35 days of cold storage at a temperature of 4 ± 1 ° C. Moringa stood out with the highest yield in relation to the mass produced, however the greatest antioxidant power was found in grape marc. The extract obtained from the red grape pomace was more efficient in inhibiting lipid oxidation. The levels of N-BVT in all treatments remained within the limit considered safe for food. The total color difference was greater in the first weeks in all treatments, emphasizing that the red grape pomace showed greater color maintenance. The color changes that occurred in the meat product pate are possibly associated with the instability of the natural antioxidant's pigmentation itself. Finally, the extracts were applied to different classes of food, such as: fermented milk, bread and chicken pate and subjected to colorimetric and sensory analysis. The word association test was applied to verify consumers' perception of products made with natural antioxidants. In this technique, blind condition and informed condition stimuli were used. The hedonic facial scale test (emojis) was applied to verify the acceptance index of the products. In the colorimetric analysis, it was found that the three products have different colors. Sensory tests reported that product acceptance was influenced by the taste that natural antioxidants attributed to products. The use of the technique in blind condition and informed conditions showed that consumers consider foods with healthier natural antioxidants. Propolis showed less acceptance in bread due to the characteristic taste that propolis provided to the product.